Visual outcomes of high-volume compared with low-volume manual small-incision cataract surgery in Nepal. Issue 8 (August 2020) - Bhatta, Subash; Patel, Poorav J.; Awasthi, Suresh; Pant, Nayana; Pant, Suresh Raj
Abstract : MSICS used in high-volume cataract surgery centers can play an important role in managing large cataract backlogs in developing countries, providing reproducible and acceptable visual outcomes. Abstract : Purpose: To study whether manual small-incision cataract surgery (MSICS) in a high-volume setting gives acceptable postoperative visual outcomes. Settings: Geta Eye Hospital, Kailali, Nepal. Design: Single-center retrospective study. Methods: One-year records of all MSICS in adult patients without any other ocular comorbidity were analyzed retrospectively. Surgical outcomes of cataract cases when surgeons performed more than 72 surgeries (high volume) in a single operating session (1 day) were compared with when fewer than 30 surgeries (low volume) were performed in a single operating session (1 day). Results: Of 23 717 cases in the study, 20 574 patients (87%) had preoperative visual acuity of less than 3/60; 15 632 patients (66%) achieved good visual outcome (uncorrected distance visual acuity of 6/18 or better) postoperatively. Patients operated during high-volume months achieved good visual outcomes in 9930 cases (66.9%) as compared with 5702 (64.3%) in low-volume months. However, 6235 patients (61.7%) operated on during high-volume days had good visual outcomes as compared with 3053 (71.4%) during low-volume days; 175 patients in the high-volume group and 73 patients in the low-volume group (1.7% each) achieved visual acuity worse than 3/60. There were comparable posterior capsular rupture rates (423 [1.78%]) during high- and low-volume months, and 21 cases (0.09%) of postoperative endophthalmitis were noted. Conclusions: MSICS can be used to reduce large cataract backlogs in developing countries as good visual outcomes could be achieved in high-volume settings if standard protocols for quality control are followed.